DEVELOPMENT OF TRADITIONAL MARKET LOCATION IN TASIKMALAYA CITY - Darmawan, Darwis (Universitas Pendidikan Indonesia, 2017)
The economic force in Tasikmalaya City is dominated by trading and processing indus-tries through trade, hotel and restaurant sector. To compensate the increase of those economic sector, the quality and quantity of traditional markets necessary to be more improved. This study aims to analyze the direction of development of traditional mar-ket location in Tasikmalaya City. This research uses descriptive analysis method. The data used are primary and secondary data collected through observation, field survey, interview, and literature study. Population and sample in this research is community around market by using Random Sampling method. Result of research indicate that development of location of Traditional Market in Tasikmalaya City is in accordance with Spatial Plan of Area (RTRW) Tasikmalaya City. The form of market development is to improve the quality of market facilities in order to compete with the super market.